Searches for Prompt R-Parity-Violating Supersymmetry at the LHC - Andreas Redelbach (Advances in High Energy Physics)
Searches for supersymmetry (SUSY) at the LHC frequently assume the conservation of R-parity in their design, optimization, and interpretation. In the case that R-parity is not conserved, constraints on SUSY particle masses tend to be weakened with respect to R-parity-conserving models. We review the current status of searches for R-parity-violating (RPV) supersymmetry models at the ATLAS and CMS experiments, limited to 8 TeV search results published or submitted for publication as of the end of March 2015. All forms of renormalisable RPV terms leading to prompt signatures have been considered in the set of analyses under review. Discussing results for searches for prompt R-parity-violating SUSY signatures summarizes the main constraints for various RPV models from LHC Run I and also defines the basis for promising signal regions to be optimized for Run II. In addition to identifying highly constrained regions from existing searches, also gaps in the coverage of the parameter space of RPV SUSY are outlined.